Mission Santa Clara fire - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the ruins of Mission Santa Clara after the October 1926 fire. A bell lies in a pile of charred debris. Through a brick archway in the background, a man is visible. Handwritten in pencil on the verso of the photograph: "Fire damaged Santa Clara Mission."